Status of Extended Threshold Wavelength Split-Off Band IR Detectors and Quantum Material-Based Extension for Room-Temperature Operation - A. G. Unil Perera; Yanfeng Lao; Tara Jabegu; Sidong Lei (Micromachines)
This paper reports possible performance improvements of split-off band infrared detectors by using novel quantum materials. The report starts by describing the development of split-off band infrared detectors based on heterostructures with extended photoresponsivity beyond the energy band gap. The design modification demonstrated a new phenomenon of extending the threshold wavelength beyond the standard wavelength threshold (λt) determined by the energy gap (Δ) and the wavelength equation λt = 1.24/Δ with the dark current still governed by the original energy gap. However, to overcome the operating temperature challenges in AlGaAs/GaAs-based devices, the perspective of van der Waals quantum materials (vdW-QM)-based IR sensors is discussed regarding the aspects of heterostructure fabrication methods, theoretical modeling, and strategies that could help to overcome these issues. Through these discussions, the review paper aims to inspire upcoming innovations in developing novel IR photodetectors capable of operating within the atmospheric window at room temperature.